Effect of Sodium Chloride on Pyrite Bioleaching and Initial Attachment by Sulfobacillus thermosulfidooxidans - Huynh, Dieu; Norambuena, Javiera; Boldt, Christin; Kaschabek, Stefan R.; Levicán, Gloria; Schlömann, Michael (Frontiers in Microbiology, 2020)
Biomining applies microorganisms to extract valuable metals from usually sulfidic ores. However, acidophilic iron-oxidizing bacteria tend to be sensitive to chloride ions which may be present in biomining operations. This study investigates the bioleaching of pyrite as well as the attachment to pyrite by Sulfobacillus (S.) thermosulfidooxidans DSM 9293T in the presence of elevated NaCl concentrations. The bacteria were still able to oxidize iron in the presence of up to 0.6 M NaCl (35 g/L), and the addition of NaCl in concentrations up to 0.2 M (~ 12 g/L) did not inhibit iron oxidation and growth of S. thermosulfidooxidans in leaching cultures within the first 7 days. However, after approximately 7 days of incubation, ferrous iron concentrations were gradually increased in leaching assays with NaCl, indicating that iron oxidation activity over time was reduced in those assays. Although the inhibition by 0.1 M NaCl (~ 6 g/L) of bacterial growth and iron oxidation activity was not evident at beginning of the experiment, over extended leaching duration NaCl was likely to have an inhibitory effect. Thus, after 36 days of the experiment bioleaching of pyrite with 0.1 M NaCl was reduced significantly in comparison to control assays without NaCl. Pyrite dissolution decreased with the increase of NaCl. Nevertheless, pyrite bioleaching by S. thermosulfidooxidans was still possible at NaCl concentrations as high as 0.4 M (~ 23 g/L NaCl). Besides, cell attachment in the presence of different concentrations of NaCl was investigated. Cells of S. thermosulfidooxidans attached heterogeneously on pyrite surfaces regardless of NaCl concentration. Noticeably, bacteria were able to adhere to pyrite surfaces in the presence of NaCl as high as 0.4 M. Although NaCl addition inhibited iron oxidation activity and bioleaching of pyrite, the presence of 0.2 M seemed to enhance bacterial attachment of S. thermosulfidooxidans on pyrite surfaces in comparison to attachment without NaCl.